Academic multiple communication in geosciences: innovation and curricular transversality at the Universidad Nacional de Río Negro - Diez, María Angélica (2018)
Fil: Diez, María Angélica. Universidad Nacional de Río Negro, Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.